Implementasi Time Division Duplex (TDD) pada Bluetooth Low Energy (BLE) dan Wi-Fi untuk Penjadwalan pada Sistem Monitoring Tanaman - Aditya Hermawan; Mochammad Hannats Hanafi Ichsan; Rakhmadhany Primananda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Wireless Sensor Network (WSN) consists of a number of small sensor nodes that are used to observe a phenomenon. Generally, a wireless sensor network is a sensor device that is connected to an embedded system or called an embedded sensor that can connect to the network and communicate with cloud servers. The device commonly used in WSN is ESP-32, which has BLE and Wi-Fi communication on a single frequency. The use of sending and receiving data at a single frequency allows the collision of sending and receiving signals that cause packet damage. This can be minimized by implementing an appropriate scheduling method. One of the scheduling methods commonly used is Time Division Duplex (TDD). The concept of TDD is to divide one frequency into several time slots, and then time slots will be allocated for receiving or sending data. Previous studies have successfully implemented TDD on large-scale mobile networks with 5G technology and implemented BLE for blood pressure monitoring. This study aims to design a gateway with TDD scheduling method. The test is carried out with a scenario of distance variation with parameters success ratio, discovery time, and delay. The variation in distance used is 1 meter to 13 meters. The success ratio parameter produces a success ratio of 84% at a distance of 1 meter and 0% at a distance of 13 meters. Then, the discovery time parameter obtained 2.36 seconds at a distance of 1 meter and 2.73 seconds at a distance of 10 meters. Finally, the delay parameters obtained an average delay of 1 second at a distance of 1 meter and 7.68 seconds at a distance of 10 meters.